Desenvolvimento e avaliação de mecanismo acondicionador de palha para descompactadores de solo em semeadura direta - Bellé, Mateus Potrich (2016)
The No-Till System is a management technique and conservation which calls for little soil disturbance, crop rotation and maintenance of vegetation cover on the surface, where the latter is the main one. However, if these prerequisites aren´t adopted completely problems such as soil compaction arise, reducing crop yields and requiring interventions such as mechanical decompression through scarification or subsoil. However, these operations reduce the vegetation cover on the surface increasing the risk of erosion. Therefore, the improvement of these tools by developing new designs for structures that provide the best adaptation of these implements to no-till system becomes necessary. Thus, the objective of this study was the comparison of six different designs, characterized by combinations of straw packaging tools, looser elements, cutting disk and its settings and clod-breaking roller, and develop a tool for packaging of this straw on the surface. The conceptions were made by combining different looser elements, packaging tools straw and soil, such as clod-breaking roller and conditioner mechanism of straws, and still exploring different disk distances to the rod for all conceptions. The results showed high potential of the design made by the conditioner mechanism straw associated with clod-breaking roller and cutting disk, maintaining high levels of straw on the surface and the disc move closer to the stem, shorter distance, provided increased strength and average drawbar power.